Group Metacognitive Therapy for Generalized Anxiety Disorder: A Pilot Feasibility Trial - Haseth, Svein; Solem, Stian; Sørø, Grethe Baardsen; Bjørnstad, Eirin; Grøtte, Torun; Fisher, Peter (Frontiers in Psychology, 2019)
Background: Individual metacognitive therapy (MCT) for generalized anxiety disorder (GAD) is well established, but only one study has investigated the effectiveness of Group MCT (g-MCT) for GAD. The aim of the current study was therefore to evaluate the feasibility and effectiveness of g-MCT for GAD within a community mental health setting whilst addressing limitations evident in the previous study. Method: The study used an open trial design, and 23 consecutively referred adults with GAD completed 10 sessions (90 minutes) of g-MCT, delivered by two therapists trained in MCT. Diagnoses were assessed by trained raters using the Anxiety Disorder Interview Schedule-IV. All patients but one had previous psychosocial treatment, and 17 (73.9%) had at least one comorbid axis-I disorder. Self-reported symptoms were assessed using the Penn State Worry Questionnaire, the Generalized Anxiety Disorder-7, and the Patient Health Questionnaire-9 at pre- and post-treatment as well as 3-month follow-up. Feasibility was assessed using rates of patients who declined group treatment in favour of individual treatment, patients not able to attend due to pre-scheduled dates for sessions, and drop-out rate. Results: Of 32 eligible participants, six patients (19%) declined g-MCT in favour of individual MCT, and three (9%) were unable to attend due to scheduling conflicts. No patients dropped out during treatment, but two patients did not complete the self-report questionnaires at 3-month follow-up. g-MCT was associated with significant reductions in worry, anxiety, depression, metacognitive beliefs, and maladaptive coping. According to the standardised Jacobson criteria for recovery, 65.2% were recovered at post-treatment, whereas 30.4% were improved and 4.3% showed no change. At 3-month follow-up, the recovery rate increased to 78.3%. Moreover, recovery rates were comparable for patients with- and without comorbidity. Number of therapist hours per patient was 6.5 and the treatment has now been implemented as a standard treatment option at the clinic. Conclusion: g-MCT for GAD is an acceptable treatment which may offer a cost-effective alternative approach to individual MCT. Recovery rates and effect sizes suggested that g-MCT could be just as efficient as individual MCT and cognitive behavioural therapy.